Implementación de sistemas de codificación en prótesis dentales para la identificación humana. - Narváez Antamba, Grace Valeria (2024)
The objective of this systematic review type research work was to analyze the feasibility of the technique of applying coding systems in dental prostheses for human identification. The study was governed by the requirements of the PRISMA protocol (26). In addition to determining the different coding systems in the application of dental prostheses for human identification, identifying the most relevant dental prosthetic materials used for forensic analysis and establishing recommendations for the use and management of labeling in dental prostheses. During the systematic search, 3 databases were used: Google Scholar, PubMed, and Science Direct. 26 high-impact articles were selected to carry out the research analysis according to the stated objectives. The collection of information for the meta-analysis within the study based on the inclusion and exclusion criteria that are governed by the year of publication (within the last 10 years), type of population (descriptive and experimental studies), free of charge (articles complete and free), language (English and Spanish) and quality (reliable databases). The result is that the labeling of removable dental prostheses are viable techniques in the human identification of people with dental appliances since ancient times, being a useful tool in resolving legal expertise when other forensic methods have failed thanks to the classification presented in their different labeling techniques, this also thanks to the resistance that prosthetic devices present in more hostile environments, the viability of forensic analysis is demonstrated. On the other hand, the importance of the study and application of forensic odontology in the general practice of professionals and students can be emphasized due to its performance in human identification.